Is restorative justice conferencing appropriate for youth offenders? - Suzuki, Masahiro (Criminology & criminal justice, 2018)
While many studies on restorative justice conferencing (RJC) for youth offenders have shown favourable outcomes such as victim satisfaction and fairness, and offender accountability and perceived legitimacy, other studies have demonstrated more problematic outcomes in terms of mutual understanding, sincerity of apology and reoffending. Given the complexity of RJC as a concept and as a process, such ‘limits’ might be attributed to the capacity and characteristics of youth offenders. To date, however, there has been little examination of developmental, cognitive or environmental impediments on the part of youth offenders in terms of achieving restorative outcomes in RJC. This article discusses the potential impacts of limited developmental and cognitive capacities of youth offenders on the RJC process and outcomes.